CONCRETE MIX ANALYSIS WITH VOLUME RATIO AND OBSERVATION OF MEDIUM STRENGTH CONCRETE CHARACTERISTICS IN THE CONSTRUCTION OF MIPA FACULTY BUILDING PATTIMURA UNIVERSITY - ABRAHAM TUANAKOTTA (CV KULTURA DIGITAL MEDIA, 2020)
The need for concrete in a project is not only in large volumes, but also in small volumes. In large volumes, the fulfillment of concrete needs in a project can be done by ordering to concrete suppliers in the form of readymix concrete. Concrete batching plants are used for concrete production of all kinds of projects such as roads, bridges, dams, airports, airports, etc. They can be equipped with one mixer or more in various capacities. The concrete mixes in the project with a volume ratio of 1:1.5:2.5 (cement: sand: crushed stone) with FAS values (0.43-0.47) for concrete quality ranging from K250 - K300. Based on this, this research aims to get the composition of the concrete mixture using a volume ratio for different FAS values and get its compressive strength. The method used in this research is the experimental method, namely planning the composition of the concrete mixture with a volume ratio of 1: 1.5: 2.5 (cement: sand: crushed stone) with FAS values (0.43-0.47) testing the compressive strength of the concrete cube test samples. With the results of the concrete compressive strength test for FAS 0.43, namely 270.525 Kg / cm³ and for FAS 0.47, namely 264 Kg / cm³.